Heat Transfer Enhancement During Water and Hydrocarbon Condensation on Lubricant Infused Surfaces - Preston, Daniel J. (Sci Rep, 2018)
Vapor condensation is routinely used as an effective means of transferring heat or separating fluids. Dropwise condensation, where discrete droplets form on the condenser surface, offers a potential improvement in heat transfer of up to an order of magnitude compared to filmwise condensation, where a liquid film covers the surface. Low surface tension fluid condensates such as hydrocarbons pose a unique challenge since typical hydrophobic condenser coatings used to promote dropwise condensation of water often do not repel fluids with lower surface tensions. Recent work has shown that lubricant infused surfaces (LIS) can promote droplet formation of hydrocarbons. In this work, we confirm the effectiveness of LIS in promoting dropwise condensation by providing experimental measurements of heat transfer performance during hydrocarbon condensation on a LIS, which enhances heat transfer by ≈450% compared to an uncoated surface. We also explored improvement through removal of noncondensable gases and highlighted a failure mechanism whereby shedding droplets depleted the lubricant over time. Enhanced condensation heat transfer for low surface tension fluids on LIS presents the opportunity for significant energy savings in natural gas processing as well as improvements in thermal management, heating and cooling, and power generation.